2021
DOI: 10.1093/jnci/djab197
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Pre- and Postdiagnosis Obesity and Endometrial Cancer Survival

Abstract: Background Disease-free and overall survival associations with anthropometric measures of obesity and changes in these exposures remain unknown among endometrial cancer survivors. Methods Endometrial cancer survivors diagnosed between 2002–2006 completed direct anthropometric measurements and self-reported lifetime weight history during in-person interviews approximately 4 months after diagnosis (peri-diagnosis) and approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…According to present knowledge, it has been proven that overweight and obesity are often associated not only with reproductive health disorders, but also with the formation of oncological diseases [7,10,14]. We analyzed the ultrasound data of the pelvic organs in our patients and found that endometrial hyperplasia was recorded in 52 (57.7%) patients with overweight and obese, and 19 (36.7%) cases were against the background of hyperestrogenemia, which may serve as a risk factor for the RQFRSDWKRORJ\ LQ WKH IXWXUH 2YHUZHLJKW DQGRU obese patients are characterized by various dyslipidemias (DLP), which are predictors of a number of cardiovascular diseases (hypertension, atherosclerosis, etc.).…”
Section: Results and Discussion Of The Studymentioning
confidence: 99%
“…According to present knowledge, it has been proven that overweight and obesity are often associated not only with reproductive health disorders, but also with the formation of oncological diseases [7,10,14]. We analyzed the ultrasound data of the pelvic organs in our patients and found that endometrial hyperplasia was recorded in 52 (57.7%) patients with overweight and obese, and 19 (36.7%) cases were against the background of hyperestrogenemia, which may serve as a risk factor for the RQFRSDWKRORJ\ LQ WKH IXWXUH 2YHUZHLJKW DQGRU obese patients are characterized by various dyslipidemias (DLP), which are predictors of a number of cardiovascular diseases (hypertension, atherosclerosis, etc.).…”
Section: Results and Discussion Of The Studymentioning
confidence: 99%
“…Although distant metastasis is exceptionally uncommon in EC, our study showed that its incidence has increased from 2010 to 2017, especially in the period during 2016-2017. It is speculated that the reasons for this increase mainly include the prevalence of obesity, 17,18 the improvements of postmenopausal screening techniques, 19 and the influence of reproductive factors. 20,21 Furthermore, this study showed that lung was the most frequent organ in metastasis and that solitary pulmonary metastasis accounted for 57.7% of all distant pulmonary metastases, which was in accordance with the report by Mao et al 5 Researchers suspect that metastatic tumor cells may infiltrate blood vessels and facilitate the development of pulmonary metastases via the iliac veins, 22 but this has not been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous reports from the Alberta Endometrial Cancer Cohort Study in which measures of obesity were associated with reduced survival. 35 , 36 Moreover, metabolic syndrome was associated with worse disease‐free and overall survival in endometrial cancer survivors. 35 …”
Section: Discussionmentioning
confidence: 99%